Saving Transition in Asia - Athukorala, Prema-Chandra; Suanin, Wanissa (The Journal of Development Studies, 2024)
This paper examines the national saving behaviour in the process of economic growth through a comparative analysis of countries in developing Asia from a historical perspective. Developing Asia provides an ideal laboratory for the study with considerable differences in the saving behaviour among countries and over time within individual countries, notwithstanding the 'model saver' image of the region that is based mainly on the experience of high-performing East Asian economies. The empirical analysis distinguishes between private and government saving rates, with specific emphasis on the former. The results of the empirical analysis are consistent with the view of a 'virtuous circle' between growth and saving, with growth initiating the saving transition. No evidence to suggest that a prior phase of promoting saving through specific policy initiatives is needed to initiate the process of growth and structural transformation. The private saving rate is also associated positively with export orientation of the economy, and net foreign capital inflows and negatively with the young dependency ratio of the population and domestic credit availability.
Keywords: Investment; Life Cycle Model; Saving; Export-Led Growth